Effect of sulphur fertilization on soil adsorption-desorption dynamics, nutrient uptake and yield of sesame in Typic Chromustert - Niharika, P; Saravana, P P; Indirani, R; Kumutha, K (Plant Science Today, 2025)
Sesame (Sesamum indicum L.), a nutrient-rich oilseed crop, held significant value in Asian diets due to its health benefits and potential to prevent various ailments. However, sesame cultivation was often hindered by poor crop establishment and imbalanced nutrient management - particularly sulphur (S). Sulphur was essential to improve both crop productivity and oilseed quality. This study aimed to evaluate the effects of sulphur fertilization on nutrient uptake and yield of sesame grown in sulphur-deficient soils (7.7 mg kg-1). A laboratory experiment was conducted to understand the adsorption-desorption dynamics of sulphur, which showed that both processes peaked at an added sulphur concertation of 1000 µg mL-1 after which a declining trend was observed. Field experiments involved the application of sulphur in the form of FeSO4 and gypsum at rates of 20, 40 and 60 kg ha-1 through soil, along with foliar spray K2SO4 (0.5 %) at 20 and 40 Days After Sowing (DAS). The treatment that combined N, P2O5 and K2O based on Soil Test Crop Response (STCR) recommendations along with 40 kg S ha-1 as FeSO4 and foliar spray application of K2SO4 (0.5 %) recorded the highest nutrient uptake (N: 63.89 kg ha-1, P: 7.27 kg ha-1, K: 44.75 kg ha-1, S: 13.44 kg ha-1) and the maximum grain and stalk yields (835 and 2550 kg ha-1 respectively). In contrast, the control treatment recorded the lowest yields. In conclusion, the combined application of sulphur through soil and foliar methods, along with balanced NPK fertilization based on STCR significantly improved sesame yield and nutrient uptake. This integrated approach offered a practical and effective solution to manage sulphur-deficient soils in sesame cultivation.